Disentangling loneliness and trust in populist voting behaviour in Europe - Francesco Berlingieri; Béatrice d'Hombres; Matija Kovacic (Global Labor Organization (GLO), 2025)
This paper explores the relationship between loneliness, trust, and populist voting across both extremes of the ideological spectrum. The contribution of this research is mainly two-fold. First, it considers different dimensions of loneliness and accounts for its predetermined component stemming from social isolation in childhood and adverse childhood experiences. Second, it disentangles the effects of loneliness and trust by incorporating actual trust behaviour from a large-scale trust game experiment conducted in 27 European member states, involving more than 25,000 individuals. The richness of the data allows to account for and disentangle the impact of competitive explanatory factors such as emotions, objective social isolation, social media use and economic preferences. The main findings suggest the following: (i) social loneliness significantly impacts populist voting, particularly on the extreme right, whereas the emotional dimension of loneliness is associated with more left-leaning, but non-populist, voting preferences; (ii) higher levels of actual trust are associated with lower support for right-wing populist parties; (iii) loneliness and trust operate through distinct channels: loneliness exerts a greater impact on women and older individuals, while trust plays a more significant role among men and middle-aged individuals, and (iv) the effect of social loneliness on support of populist parties is significantly attenuated in contexts with a history of recurrent economic crises, suggesting a potential experience-based learning mechanism.
Keywords: D72; D91; P00; C91; Z13; 330; Loneliness; interpersonal trust; political polarisation; populism